Model Bowling Monster Untuk Meningkatkan Motivasi Belajar Siswa Sekolah Dasar - Devi Wahyu Ertanti (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2020)
The implementation of learning in the classroom is not only aimed at shaping students' cognitive abilities, but these activities also synergize the cognitive, psychomotor, and affective abilities that students have to develop life skills that can be used by students in everyday life. Attractive learning models can help increase student motivation in learning. The purpose of this study was to measure the effectiveness of the application of the bowling Monster learning model to increase student motivation in Puloniti elementary school, Bangsal, Mojokerto. The Bowling Monster model is packaged in learning in such a way that it becomes learning by playing, with the aim of students not experiencing pressure in understanding the subject matter, but the child feels that they are playing and also learning to understand the material. With the application of the bowling monster model, students' motivation to learn in mathematics subject matter of simple fractions increases.